The Influence Of Digital Transformation, Soft Skills, And Labor Market Considerations On The Perceptions Of Accounting Students To Become Public Accountants - Dwi Putra, Rifal; Yudi, Yudi; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2025)
This study aims to examine the effect of digital transformation, soft skills, and labor market considerations on the perceptions of accounting students in choosing a career as a public accountant. The method used is quantitative with a causal associative approach. The data were collected through a questionnaire of 158 Jambi University accounting students class of 2021 and analyzed using multiple linear regression with the help of SPSS version 25. The results of the study partially show that digital transformation has no effect on the perception of accounting students to become public accountants. Meanwhile, soft skills and labor market considerations have a positive effect on student perceptions. Simultaneously, the three variables affect student perceptions in determining career choices as public accountants. These findings indicate that although technology is an important part of the accounting profession, students are more influenced by soft skills readiness and labor market conditions in shaping their perceptions and interest in a career as a public accountant.